ANALISIS FAKTOR HUMAN ERROR, HEWAN, CUACA DAN RAMBU-RAMBU LALU LINTAS TERHADAP TERJADINYA KECELAKAAN LALU-LINTAS PADA JALAN RAYA DENPASAR-GILIMANUK KABUPATEN JEMBRANA BALI - I Gede Rivaldy Aryana Gita Nanda; Kusdibyo Kusdibyo; Supriyanto Supriyanto (FEB Universitas Maritim Semarang, 2022)
Traffic accidents are influenced by several factors including human error, animals, weather, traffic signs. Of the four, have an influence on traffic accidents with satisfactory results. The purpose of this study was to determine whether there was an influence of Human error, Animals, Weather, and Traffic Signs on traffic accidents on the Denpasar-Gilimanuk highway, Jembrana Regency, Bali. In this study, the research population is motorized vehicle users who cross the Denpasar-Gilimanuk highway, Jembrana Regency by taking a sample system with a total of 93 respondents (samples). The variables in this study consisted of: Human error (X1), Animals (X2), Weather (X3), Traffic signs (X4) and the dependent variable was Traffic Accident (Y). The research model is multiple linear regression analysis. The results of the analysis using the statistical tool SPSS V.25 program obtained multiple linear regression equations Y = -1.530+0,313X1+0,227X2+0,258X3+0,318X4+µ. Shows that, based on empirical facts (the results of filling out the questionnaire) and multiple linear regression results show that the Human error variable (X1) has a t count of 3.680 and a t table of 1.98729 then H1 is accepted and significant, animals (X2) have a t count of 2,035 and t table of 1,98729 then H2 is accepted and significant, weather (X3) has a t count of 2.852 and t table of 1.98729 then H3 is accepted and significant, traffic signs (X4) has a t count of 4.618 and t table of 1.98729 then H4 is accepted and significant. In the coefficient of determination test (R Square) the Adjust R Square value of 0.633 means that 63.3% of the variation in the dependent variable of traffic accident factors can be explained by the independent variables of human error, animals, weather, traffic signs. While the remaining 36.7% is explained by other reasons outside the variables studied.